Anticholinesterase Activity of Methanolic Extract of Amorpha fruticosa Flowers and Isolation of Rotenoids and Putrescine and Spermidine Derivatives - Jankovská, Dagmar; Jurčová, Nikol; Kubínová, Renata; Václavík, Jiří; Švajdlenka, Emil; Mascellani, Anna; Maršík, Petr; Bouzková, Kateřina; Malaník, Milan (Plants, 2024)
Five putrescine and spermidine derivatives (1-5) together with five rotenoids (6-10) were isolated from a methanolic extract of the flowers of A. fruticosa that displayed promising inhibition of 76.0 ± 1.9% for AChE and 90.0 ± 4.0% for BuChE at a concentration of 1 mg/mL. Although the anticholinesterase activities of the isolated compounds did not reach that of galantamine, molecular docking revealed that all-trans-tri-p-coumaroylspermidine and trans-trans-cis-tri-p-coumaroylspermidine showed binding poses mimicking the known inhibitor galantamine and thus could serve as model molecules in future searches for new AChE and BuChE inhibitors.